PROBLEMATIKA NIKAH SIRRI DI KALANGAN TENAGA KERJA KASUS DI BATUKLIANG LOMBOK TENGAH - Muhasim, Ahmad (LP2M IAIN Mataram, 2014)
This research is aimed to decipher and to find some problems of unrecorded marriage among the manpower in Batukliang Central Lombok. In order to do so, qualitative research approach with field research model is necessary, so as to library research. The subjects of this research are determined through purposive sampling. Meanwhile in data gathering, observation method, interview, and documentation are applied. Thus the gathered data are analyzed through inductive analysis. This study shows that: first, unrecorded marriage among Indonesian migrant workers and/or former Indonesian migrant workers in Batukliang Sub district, Central Lombok is not merely a âmythâ. it is evidently proven through the fact that there are some unrecorded marriage conducted by Indonesian migrant workers in Batukliang, Second, the motive behind this unrecorded marriage are varies such as; (1) the costs, (2) Pregnant without marital relationship, (3) wrong perception upon marriage recording as a formal prerequisite of marriage, but it is legal before the religion in committing marriage without civil recording; (4) Negligence of the Groom or Husband party upon recording his marriage to the appointed agency; (5) culture of divorce ;(6) underage married: (7) state of lying upon the fellow villagers. Third, there are two impacts or effects of unrecorded marriage upon the TKI (or former TKI), both are negative and positive. The former is with unrecorded marriage, marriage procession can be executed without high cost. Meanwhile the latter is more prominent than the positive one i.e. 1) negligence upon the rights of wife during the process of and after divorce. 2) Negligence upon the rights of the children who born from unrecorded marriage